Editing Niels W. Gade’s Cantata Comala: Some problems regarding final intentions - Teich Geertinger, Axel (Danish Yearbook of Musicology, 2016)
The attempt to represent final authorial intentions in some form is still a common principle in Scandinavian music editions, despite the fact that similar principles have long been criticized in the field of textual criticism. The article points out some of the general problems of such concepts, including the divergent forces of authority and finality. The recent difficulties of editing Niels Wilhelm Gade’s cantata Comala under the Gade Edition’s Fassung letzter Hand perspective illustrate these problems. The article suggests that aspects such as reception history or the composer’s authority alone may be better points of departure for future editions than concepts focusing on temporality.